2013
DOI: 10.3857/roj.2013.31.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated three-dimensional conformal radiotherapy for medically inoperable early stage non-small-cell lung cancer

Abstract: PurposeThe purpose of this study was to assess the clinical outcomes of hypofractionated radiotherapy (HFRT) with three-dimensional conformal technique for medically inoperable patients with early stage non-small-cell lung cancer (NSCLC) and to evaluate prognostic factors.Materials and MethodsWe performed a retrospective review of 26 patients who underwent HFRT for early stage NSCLC between September 2005 and August 2011. Only clinical stage T1-3N0 was included. The median RT dose was 70 Gy (range, 60 to 72 Gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
(40 reference statements)
1
9
0
Order By: Relevance
“…The largest retrospective Canadian study reported a 2-year LC rate of 76.2% in 118 patients following a total dose of 48-60 Gy in 12-15 fractions, in which most patients received 48 Gy (59.7%) or 52 Gy (37.1%) [8]. Lee et al [14] reported a 2-year LC rate of 74.6% in 26 patients following median 70 Gy (range, 60 to 72 Gy) in 15-18 fractions. In the current study, the authors achieved a 2-year LC rate of 75.2% in group 3 following 60 Gy in 15 fractions, which was quite comparable with other studies mentioned above [8,13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest retrospective Canadian study reported a 2-year LC rate of 76.2% in 118 patients following a total dose of 48-60 Gy in 12-15 fractions, in which most patients received 48 Gy (59.7%) or 52 Gy (37.1%) [8]. Lee et al [14] reported a 2-year LC rate of 74.6% in 26 patients following median 70 Gy (range, 60 to 72 Gy) in 15-18 fractions. In the current study, the authors achieved a 2-year LC rate of 75.2% in group 3 following 60 Gy in 15 fractions, which was quite comparable with other studies mentioned above [8,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [14] reported a 2-year LC rate of 74.6% in 26 patients following median 70 Gy (range, 60 to 72 Gy) in 15-18 fractions. In the current study, the authors achieved a 2-year LC rate of 75.2% in group 3 following 60 Gy in 15 fractions, which was quite comparable with other studies mentioned above [8,13,14]. Actually, the 2-year LC rate following 60 Gy in 15 fractions as in the current study was numerically superior to those achieved by the authors following 60 Gy in 20 fractions: 56.9% in the current study (as in group 2); and 57.9% in a previous study [7].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the radiation doses were 57, 60, 63 and 66 Gy in 11.8%, 20.6%, 44.0% and 23.6% of patients, respectively. The total dose of 66 Gy in 22 fractions was the maximum recommended dose for this study based on hypofractionated and SBRT studies, 12,18 which had less restrictive criteria in terms of tumour size and late toxicity and proposed biological equivalent doses in the range of 83.2-146 Gy.…”
Section: Radiotherapy Techniquementioning
confidence: 99%
“…Some studies of HFRT using various radiation-dose schedules resulted in improved outcomes beyond those achieved with conventionally fractionated RT. [11][12][13] The purpose of this study was to assess the toxicity and clinical outcome of dose-escalation HFRT with 3D RT for medically inoperable early-stage NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that RT dose escalation improves locoregional control in NSCLC (Mehta et al, 2001, Rengan et al, 2004, Bradley et al, 2005, Rosenzweig et al, 2005, Ding et al, 2012, Lee et al, 2013, Liu et al, 2013, Zheng et al, 2013. Recently, intensity-modulated RT has been proposed as an effective modality to facilitate dose escalation to target volumes while sparing normal surrounding tissues.…”
Section: Introductionmentioning
confidence: 99%